EKSTRAK BUAH NANAS TERHADAP JUMLAH TOTAL LEUKOSIT DAN NEUTROFIL IKAN LELE (Clarias batrachus) YANG DIINFEKSI DENGAN Aeromonas hydrophila - Ratna Widyawati; Dyah Widhowati; Dhia Nadhifa (VITEK : Bidang Kedokteran Hewan, 2020)
The present research to determine the Extract of Pineapple (Ananas comosus) on the survival of catfish infected with A. Hydrophila. The main problem of cultivation of catfish (C. batrachus) is a disease caused by the bacterium Aeromonas hydrophila.Catfish (Clarias batrachus) is a freshwater fish that has several advantages, one of which is a high nutritional content. Test animals used were catfish measuring 15-20cm with a body weight of ± 250gr. Challenge test by injecting A. hydrophila suspension with a dose of 108sel / mm3 as much as 0.1mm intramuscularly. Observations were made for 7 days after infection which included the total number of leukocytes and neutrophils. This study was divided into 5 treatment groups with 5 replications, namely P1 (positive control), P2 (0.1%), P3 (0.3%), P4 (0.5%), P5 (0.7%) and soaking Pineapple Fruit Extract for 24 hours. Data analysis in this study used one way ANOVA statistical test. The results showed symptoms of catfish attacked by Aeromonas hydrophila including increased total number of leukocytes and neutrophils and ulceration in catfish. Soaking effect Pineapple fruit extract 0.5% effective dose can reduce the total number of leukocytes and 0.7% effective dose can reduce the total number of neutrophils.